Triangulation de Delaunay et metrique riemannienne. Applications aux maillages elements finis - Borouchaki, Houman; George, Paul Louis (European Journal of Computational Mechanics, 1996)
This paper describes the extension of the classical Delaunay method in the case where a riemannian context is specified.